Gross anatomy of the skeleton of neonates of the Orinoco Matamata turtle (Chelus orinocensis) - Liliana Andrea Valencia-Flórez; Luz Natalia Franco-Montoya; Lynda J. Tamayo-Arango; Claudia P. Ceballos (PLoS ONE, 2026)
The Orinoco Matamata turtle ( Chelus orinocensis ) was described in 2020, representing the second evolutionary lineage within the genus Chelus . The anatomy of this species has not been described, and such information is essential for understanding its biology, ecology, and for its potential relevance in clinical diagnosis. This research provides the first description of the macroscopic morphology of the skeletal system in neonates of the Orinoco Matamata turtle. A group of confiscated turtles was donated from the Alexander von Humboldt institute to our university for academic purposes. From this group, we obtained the skeleton of ten individuals, which measured between 51–80 mm of straight carapace length. Then, the skeletons of the two largest individuals were disarticulated to describe each bone in detail based on anatomical atlases and turtle osteological guides. Bones from the cranium, mandible, hyoid apparatus, and the axial and appendicular skeletons were identified and photographed. Compared to other turtle species, some bones were absent, not fully ossified, or unusually well developed at this early life stage, likely reflecting ecological adaptations. Further ontogenetic studies on skeletal ossification are important to fully understand the evolutionary history and functional adaptations of this species.